MiR‐30e‐5p represses angiogenesis and metastasis by directly targeting AEG‐1 in squamous cell carcinoma of the head and neck. Issue 2 (30th December 2019) - Zhang, Shuiting; Li, Guo; Liu, Chao; Lu, Shanhong; Jing, Qiancheng; Chen, Xiyu; Zheng, Hua; Ma, Huiling; Zhang, Diekuo; Ren, Shuling; Shen, Zhe; Wang, Yunyun; et al.
Abstract: Metastasis is a critical determinant for the treatment strategy and prognosis in patients with squamous cell carcinoma of the head and neck (SCCHN). However, the mechanisms underlying SCCHN metastasis are poorly understood. Our study sought to determine the key microRNA and their functional mechanisms involved in SCCHN metastasis. For The Cancer Genome Atlas (TCGA) data analysis, quantitative PCR was used to quantify the level of miR‐30e‐5p in SCCHN and its clinical significance was further analyzed. A series of in vitro and in vivo experiments were applied to determine the effects of miR‐30e‐5p and its target AEG‐1 on SCCHN metastasis. A mechanism investigation further revealed that AEG‐1 was implicated in the angiogenesis and metastasis mediated by miR‐30e‐5p. Overall, our study confirms that miR‐30e‐5p is a valuable predictive biomarker and potential therapeutic target in SCCHN metastasis. Abstract : Valuable predictive biomarkerPotential therapeutic targetMetastasis related gene